Start-up subsidies in East Germany: finally, a policy that works? - Marco Caliendo (Institute for the Study of Labor (IZA), 2008)
The German government has spent between 7bn and 11bn Euro per year on active labor market policies (ALMP) in East Germany in the last decade. The effectiveness of the most important programs (in terms of participants and spending) such as job-creation schemes and vocational training has been evaluated quite thoroughly in recent years. The results are disappointing, indicating that nearly all of these 'traditional' programs have to be rated as a failure. In light of these findings, policies to encourage unemployed people to become self-employed gained increasing importance. We present first evidence on the effectiveness of two start-up programs in East Germany. Our findings even though partly preliminary - are rather promising, showing that these programs increase employment chances and earnings of participants. Hence, start-up subsidies might work even in a labor market with structural problems such as the one in East Germany.
Keywords: J68; 330; Start-up subsidies; evaluation; effectiveness; East Germany; self-employment; Arbeitsmarktpolitik; Selbstständige; Subvention; Unternehmensgründung; Wirtschaftsförderung; Wirkungsanalyse; Neue Bundesländer